2003
DOI: 10.1089/154099903322643884
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Trauma and Pregnancy: A Conceptual Framework

Abstract: In this paper, we propose that a history of sexual traumatization is associated with pregnancy complications and poor pregnancy-related outcomes. We further hypothesize that this relationship is mediated by the sequelae of trauma (psychopathology, health problems, and increased negative health behaviors). We review the literature linking sexual trauma with psychopathology, health, and health behavior and then outline the impact of these variables on pregnancy. Based on this review, we draw conclusions about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 90 publications
1
21
0
Order By: Relevance
“…Recommendations are summarized and adapted from two authors who are well known researchers and professionals on the selected topic; von Sydow [7] and Leeman et al [79].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recommendations are summarized and adapted from two authors who are well known researchers and professionals on the selected topic; von Sydow [7] and Leeman et al [79].…”
Section: Resultsmentioning
confidence: 99%
“…Recommendations for taking a sexual history and giving a patient sexual advice in pregnancy or postpartum [7] Research has shown [7] that couples wish to receive more information about bodily changes and sexuality postpartum, and that counselling has been helpful. Leeman et al [79] divides a clinical approach for prevention, evaluation and treatment of postpartum sexual concerns into three parts based on prenatal care, postpartum and postnatal care (see Table 4]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations